Efforts to Improve Student Learning Outcomes in the Material of Recognizing the Alphabet through Scramble Type Cooperative Learning at RA Al Mansyuriyah Probolinggo - Humaima; Heni Astutik (Journal of Action Research in Islamic Education, 2025)
The purpose of this study is to improve student learning outcomes in the material of recognizing the alphabet through cooperative learning type Scramble. The method used in this study is Classroom Action Research consisting of two cycles, and each cycle consists of: Planning, Implementation, Observation, and reflection. The subjects of this study were students of RA Group B RA Al Mansyuriyah Leces Probolinggo. Data were collected using test and observation techniques. The test was used to measure students' ability in recognizing the alphabet, while observation was used to analyze the learning activities of teachers and students in the learning process. The collected data were then analyzed using a descriptive statistical approach. The results showed that Cooperative Learning Type Scramble can improve the learning outcomes of students in recognizing the alphabet material of RA Group B RA Al Mansyuriyah Leces Probolinggo. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 48.71%, the first cycle 66.39% and in the second cycle it increased to 89.66%. Furthermore, the researcher recommends: (1) Teachers who encounter the same difficulties can apply Scramble Type Cooperative Learning to improve Learning Outcomes. (2) In order to obtain maximum results, it is hoped that teachers will make Scramble Type Cooperative Learning more interesting and varied.